Zur Krümmungstheorie im Stützelementenraum - Bliznikas, V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Близникас. К теории кривизны пространства опорных элементов V. Bliznikas. Atraminių elementų erdvės kreivumo teorijos klausimu